Formation of the density profile and its effects on the properties of fiberboard - Wong, Ee Ding; Zhang, Min; Wang, Qian; Han, Guangping; Kawai, Shuichi (Springer Japan, 2000)
Two main types of fiberboards were produced using lauan (Shorea spp.) fibers with an isocyanate resin as the binder; fiberboard with a flat, homogeneous (homoprofile), and typical U-shaped (conventional) density profile along the board thickness. The processing parameters included manipulation of mat moisture content distribution, press closing speed, and hot pressing method. The results are summarized as follows: (1) A larger variation was observed in the peak density (PD) and core density (CD) of fiberboards at 0.5g/cm 3 mean density (MD) level than in those at 0.7g/cm3. Generally, PD showed a greater variation than CD, irrespective of MD level. (2) Boards produced using two-step hot pressing recorded substantially higher PD with reduced CD. (3) Multiple regression analysis showed that CD and PD could be calculated based on the other profile defining factors, and a rough estimation for peak distance and gradient factor was possible. (4) Based on static bending, conventional fiberboard had a higher modulus of rupture (MOR) than the homo-profile board but a similar modulus of elasticity (MOE). (5) At 0.5g/cm3 the MOR and dynamic MOE of fiberboard increased by up to 67% and 62%, respectively, when the PD increased from 0.5 to 1.07g/cm 3. Similarly, an increase of PD from 0.7 to 1.1g/cm3 resulted in corresponding increases of 55% and 34% in the MOR and dynamic MOE of 0.7g/cm3 boards. (6) The internal bond strength and screw withdrawal resistance were almost entirely dependent on the CD and MD, respectively. (7) Homo-profile fiberboards registered higher thickness swelling and water absorption than conventional fiberboards throughout the dry/wet conditioning cycle.